Desarrollo de una aplicación para dispositivos móviles de servicios de socorro, s.o.s y emergencias para la ciudad de Loja mediante la utilización de mapas. - Palacios Blacio, Luis Arturo (2014)
This degree's work shows the process of creating an emergency mobile application for Loja city by using maps; in which the architecture is based on an Android client that requests through a database using web services, it allows us to see the map of the points of interest as well as the user's current location. The Android application allows the user to make emergency calls, check out the emergency services by categories, see the main points on the map with their descriptions, the user can also see and hear the shortest route to get to the Points of interest (POI), and know the 10 nearest points related to the user’s geographical location as well. With the website you can manage points of interest as well as the user's (client) and administrator's information. This website was designed taking account the marketing of this application, which allows the user (client) to log in and manage his/her business partially. Using the software development methodology ICONIX it was possible to know the problematic through a preliminary analysis by applying the scientific, deductive, inductive and synthetic analytical methods; and techniques such as: survey and summary. In the design phase the development of UML diagrams allowed to do a good coding job in the implementation stage, reaching the requirements and goals of the project. The results of the white-box and the black box testing that was made to the website, the Android application and Web Services testing are shown. This project has a technical, economic and environmental valuation, where the justification of this research is indicated. In addition, the conclusions and recommendations are shown.